A Model for the Apparent Gas Permeability of Shale Matrix Organic Nanopore Considering Multiple Physical Phenomena - Guo, Wei; Zhang, Xiaowei; Yu, Rongze; Kang, Lixia; Gao, Jinliang; Liu, Yuyang (Frontiers in Earth Science, 2022)
Multiple physical phenomena affect the flow of shale gas in nanoscale pores. However, these phenomena are not well understood, and a unified mathematical description is still not available. A model for the apparent gas permeability of the nanopores of an organic matrix is developed in this study, considering the effects of multiple physical phenomena in matrix pores on gas transport, including matrix shrinkage, stress sensitivity, adsorption layer thinning, gas slip, Knudsen diffu-sion, surface diffusion of adsorbed gas, the confinement effect and the real gas effect. The apparent permeability of the shale matrix first decreases and then gradually increases with decreasing pore pressure. Matrix shrinkage, Knudsen diffusion, the slip effect and surface diffusion gradually in-crease as the pore pressure decreases. These four effects compensate for the decrease in the per-meability from stress sensitivity and the presence of adsorption layers while significantly increas-ing the permeability, such that the average apparent permeability loss decreases from 58.2% to 11%. With decreasing pore radius, the contribution of slip flow to the apparent permeability decreases, whereas the those of Knudsen diffusion and surface diffusion gradually increase. Real gas and confinement effects on the permeability increase significantly with decreasing pore radius and in-creasing pore pressure. For a 5-nm pore radius, real gas and confinement effects together increase the apparent gas permeability by 13.2% on average, whereas the confinement effect alone increases the permeability of pores with a 1-nm radius by 61.3% on average.